Contrastive Analysis and the Teaching of the French Sound System - Abdul Majid, Zainab Binti (Journal of Modern Languages, 2017)
This paper attempts to consider the underlying assumptions and rationale behind the contrastive analysis hypothesis (CA). It also considers the CA hypothesis as a methodological tool in teaching the French sound system to Malay learners. The paper discusses specifically the various controversial claims made for CA and its implications on pedagogy, in addition to study the direct application of CA as a possible linguistic strategy in predicting and locating phonological errors among Malay learners of French as a foreign language.